THE INFLUENCE OF MOTIVATION AND SELF EFFICACY ON EMPLOYEE PERFORMANCE THROUGH WORK DISCIPLINE AS AN INTERVENING VARIABLE AT PT. PUPUT TANI INDEPENDENT - Faisal Riza; Sukaria Sinulingga; Sugih Arto Pujangkoro (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This research aims to find out how much influence motivation and self-efficacy have on employee performance through work discipline as an intervening variable at PT. Puput Tani Mandiri. The type of research is quantitative research. The population in this study were all employees of PT. Puput Tani Mandiri, totaling 80 people, the entire number will be used as a sample, so the sample in this study is 80 respondents. The method used is Structur Equation Modeling (SEM) with Partial Least Square (PLS) 3.0. Based on the research results, it can be concluded that there is a positive and significant influence of motivation on work discipline, there is a positive and significant influence of self-efficacy on work discipline, there is a positive and significant influence of motivation on employee performance, there is a positive and significant influence of self-efficacy on employee performance, there is an influence positive but not significant work discipline on employee performance, there is a positive but not significant influence of motivation on employee performance through work discipline and there is a positive but not significant influence of self-efficacy on employee performance through work discipline.